Detailed behavioral assessment promotes accurate diagnosis in patients with disorders of consciousness - Gilutz, Yael; Lazary, Avraham; Karpin, Hana; Vatine, Jean-Jacques; Misha, Tamar; Fortinsky, Hadassah; Sharon, Haggai (Frontiers in Human Neuroscience, 2015)
Introduction: Assessing the awareness level in patients with disorders of consciousness (DOC) is made on the basis of exhibited behaviors. However, since motor signs of awareness (i.e. non-reﬂex motor responses) can be very subtle, differentiating the vegetative from minimally conscious states (which is in itself not clear-cut) is often challenging. Even the careful clinician relying on standardized scales may arrive at a wrong diagnosis. Aim: To report our experience in tackling this problem by using two in-house use assessment procedures developed at Reuth Rehabilitation Hospital, and demonstrate their clinical significance by reviewing two cases. Methods: 1.Reuth DOC Response Assessment (RDOC-RA) –administered in addition to the standardized tools, and emphasizes the importance of assessing a wide range of motor responses. In our experience, in some patients the only evidence for awareness may be a private specific movement that is not assessed by standard assessment tools. 2. Reuth DOC Periodic Intervention Model (RDOC-PIM) - Current literature regarding assessment and diagnosis in DOC refers mostly to the acute phase of up to one year post injury. However, we have found major changes in responsiveness occurring one year or more post-injury in many patients. Therefore, we conduct periodic assessments at predetermined times points to ensure patients are not misdiagnosed or neurological changes overlooked. Results: In the first case the RDOC-RA promoted a more accurate diagnosis than that based on standardized scales alone. The second case shows how the RDOC-PIM allowed us to recognize late recovery and promoted reinstatement of treatment with good results. Conclusions: Adding a detailed periodic assessment of DOC patients to existing scales can yield critical information, promoting better diagnosis, treatment and clinical outcomes. We discuss the implications of this observation for the future development and validation of assessment tools in DOC patients.